Effect of traffic noise statistical distribution on LAeq,T measurement uncertainty - Wszołek, Tadeusz; Kłaczyński, Maciej (Archives of Acoustics, 2014)
The study of traffic noise at roads and highways are performed in accordance with reference methodologies adopted as implementation to the Law on Environment Protection. The choice of applicable methodology should be based on measurement quality analysis for each particular case. While estimating the measurement uncertainty it is assumed that results are subject of normal distribution. Such solution raises some doubts or even reservations. Therefore, in the present paper the real statistical distribution of road level noise is examined while a probe of its influence on value of uncertainty of executed measurements is undertaken.